Overview of Anti-Tuberculosis Treatment Compliance in Pulmonary Tuberculosis Patients - Rohmatika, Julia; Aisyah, Popy Sity; Gartika, Nina (The Indonesian Institute of Science and Technology Research, 2024)
This research was motivated by an increase in pulmonary tuberculosis cases in 2022 of 10% and cases of loss to follow-up treatment of 11.25%. This research aimed to determine the description of Anti-TB treatment compliance in pulmonary tuberculosis patients at the Pameungpeuk Community Health Center. This research method uses descriptive quantitative with a cross-sectional design. The instrument used the MARS-5 questionnaire with 120 pulmonary tuberculosis patient respondents who received treatment at the health center. The sampling technique uses a Total sampling technique with criteria for patients undergoing treatment for a minimum of three months from 17-74 years. The research results were obtained from univariate analysis with the results that most were female (52.5%), almost half were in their late teens (32.5%), most had a high school education (60%), almost half the length of treatment was in the intensive phase (48 .3%), most experienced side effects (64.2%), most underwent routine examinations (75%), most had treatment supervision (60%), high compliance (58.3%), moderate compliance (41, 7%). It can be concluded that compliance is influenced by age, education, treatment supervision, side effects, length of treatment, routine check-ups, and gender and it is hoped that community health centers can optimize educational strategies for handling side effects to obtain maximum compliance results.